Contact precautions for MRSA and VRE: where are we now? A survey of the Society for Healthcare Epidemiology of America Research Network - Elise Martin; Daniel J. Morgan; Rachel Pryor; Gonzalo Bearman (Cambridge University Press, 2024)
Abstract Objective: Contact precautions for methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) have limited data on efficacy and have been associated with patient harm. Still, a 2015 Society for Healthcare Epidemiology of America (SHEA) Research Network (SRN) survey showed only 7% of hospitals discontinued routine MRSA/VRE contact precautions. The study objectives were to identify the current proportion of hospitals that have discontinued routine MRSA/VRE contact precautions and motivations for change. Design: An online survey was conducted of the SRN on current use and views of contact precautions for MRSA/VRE in each facility. An initial survey followed by 2 reminders was sent between 5/18/2021 and 6/9/2021. Participants: SRN facilities. Results: The response rate was 43% (37/87) of facilities surveyed and 35% of respondents were not routinely using contact precautions for MRSA and VRE. The most frequently reported reason for discontinuing contact precautions was research on the safety of discontinuing contact precautions without an increase in healthcare-associated infections (reported for 92% of facilities for MRSA and 100% for VRE). Of those using contact precautions, the most frequently reported reason to continue was a lack of safety data for discontinuation (MRSA 58% and VRE 46%). Most of those continuing contact precautions were interested in using contact precautions differently in their facility (MRSA 63% and VRE 58%). Conclusions: Over one in three healthcare facilities surveyed do not use contact precautions for MRSA or VRE. Most facilities choosing to continue contact precautions are interested in a different implementation strategy.